Switching plastic crystals of colloidal rods with electric fields - Liu, B.; Besseling, T; Hermes, M.; Demirors, A.F.; Imhof, A.; van Blaaderen, A. (Nature Research, 2014)
When a crystal melts into a liquid both long-ranged positional and orientational order are lost, and long-time translational and rotational self-diffusion appear. Sometimes, these properties do not change at once, but in stages, allowing states of matter such as liquid crystals or plastic crystals with unique combinations of properties. Plastic crystals/glasses are char- acterized by long-ranged positional order/frozen-in-disorder but short-ranged orientational order, which is dynamic. Here we show by quantitative three-dimensional studies that charged rod-like colloidal particles form three-dimensional plastic crystals and glasses if their repulsions extend significantly beyond their length. These plastic phases can be reversibly switched to full crystals by an electric field. These new phases provide insight into the role of rotations in phase behaviour and could be useful for photonic applications.